2004
DOI: 10.1183/09031936.04.10004904
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of post-pneumonectomy lung growth in adult mice

Abstract: A model of inducible expansion of the gas exchange area in adult mice would be ideal for the investigation of molecular determinants of airspace regeneration in vivo. Therefore, the post-pneumonectomy (post-PNX) compensatory lung growth in adult C57BL/6 mice was characterised in this study.Mice underwent left-sided PNX. Right lung volume was assessed on days 1, 3, 5, 7, 10 and 21 after PNX, and total DNA and cellular proliferation of the right lung were determined. Lung histology was studied using immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
101
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 30 publications
16
101
0
Order By: Relevance
“…These data broadly outline the sequence of events spanning several months during post-pneumonectomy compensation in large animal species. In comparison, in rodents, the time course of post-pneumonectomy lung growth is considerably shorter [23] and the intense cellular response heightens susceptibility to tumourigenesis as well as metastasis [24,25]. It is probable that similar biochemical and molecular pathways are re-deployed during post-pneumonectomy alveolar growth as occurs during development, although in analysis by the present author's group of selected molecular pathways in the dog, compensatory growth does not exactly replicate developmental patterns of expression [26][27][28].…”
Section: Pneumonectomy: a Model Of Compensatory Lung Growthmentioning
confidence: 99%
“…These data broadly outline the sequence of events spanning several months during post-pneumonectomy compensation in large animal species. In comparison, in rodents, the time course of post-pneumonectomy lung growth is considerably shorter [23] and the intense cellular response heightens susceptibility to tumourigenesis as well as metastasis [24,25]. It is probable that similar biochemical and molecular pathways are re-deployed during post-pneumonectomy alveolar growth as occurs during development, although in analysis by the present author's group of selected molecular pathways in the dog, compensatory growth does not exactly replicate developmental patterns of expression [26][27][28].…”
Section: Pneumonectomy: a Model Of Compensatory Lung Growthmentioning
confidence: 99%
“…If the entire left lobe of a mouse lung is removed, total lung volume is restored within 3 weeks by compensatory growth of the right lung. Detailed stereological analysis has shown that this compensatory growth involves both expansion of remaining alveoli and the formation of new alveolar units (neoalveolarization; Voswinckel et al, 2004;Fehrenbach et al, 2008). In contrast, many chronic injuries are not repairable and can lead to lung conditions, such as emphysema in which alveolar units are lost.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pneumonectomy-induced injury, in which ~50% of the lung is removed, leads to a global increase in cell proliferation and re-establishment of overall respiratory capacity. Evidence exists for both expansion of certain stem/progenitor populations and coordinated proliferation of cell Development (2014Development ( ) doi:10.1242 lineages to expand existing lung tissue (Voswinckel et al, 2004;Hoffman et al, 2010;Eisenhauer et al, 2013). However, the underlying mechanisms related to such a dramatic increase in lung size and capacity still remain unclear.…”
Section: General Mechanisms and Pathways Of Lung Regenerationmentioning
confidence: 99%